1998
DOI: 10.1074/jbc.273.48.31829
|View full text |Cite
|
Sign up to set email alerts
|

Low Reserve of Cytochrome c Oxidase Capacity in Vivo in the Respiratory Chain of a Variety of Human Cell Types

Abstract: The question of whether and to what extent the in vivo cytochrome c oxidase (COX) capacity in mammalian cells exceeds that required to support respiration is still unresolved. In the present work, to address this question, a newly developed approach for measuring the rate of COX activity, either as an isolated step or as a respiratory chain-integrated step, has been applied to a variety of human cell types, including several tumor-derived semidifferentiated cell lines, as well as specialized cells removed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
162
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 46 publications
14
162
0
Order By: Relevance
“…The observation mentioned above of a slight, although apparently significant, delay in the kinetics of decrease in the endogenous respiration rate relative to the kinetics of decrease in TMPD-dependent respiration rate could reflect an excess of COX capacity over that required to support the normal endogenous respiration. In fact, recent studies have demonstrated that, in a variety of human cell types analyzed, including fibroblasts and myoblasts, there is in vivo a relatively low excess of COX capacity (19,21). In the present work, the TMPD-dependent respiration rate had been measured in naive uncoupled Jurkat cells, and found to be ϳ33% higher than the endogenous uncoupled respiration rate (Fig.…”
Section: Decrease In Endogenous and Tmpd-dependent Respirationmentioning
confidence: 93%
“…The observation mentioned above of a slight, although apparently significant, delay in the kinetics of decrease in the endogenous respiration rate relative to the kinetics of decrease in TMPD-dependent respiration rate could reflect an excess of COX capacity over that required to support the normal endogenous respiration. In fact, recent studies have demonstrated that, in a variety of human cell types analyzed, including fibroblasts and myoblasts, there is in vivo a relatively low excess of COX capacity (19,21). In the present work, the TMPD-dependent respiration rate had been measured in naive uncoupled Jurkat cells, and found to be ϳ33% higher than the endogenous uncoupled respiration rate (Fig.…”
Section: Decrease In Endogenous and Tmpd-dependent Respirationmentioning
confidence: 93%
“…1C). In situ measurement of COX activity by histochemical staining is an indication for respiratory capacity (11)(12)(13). Furthermore, ROS accumulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitor titrations of COX activity have shown that in some cell types a 50 -60% reduction in COX activity does not significantly inhibit metabolic respiratory function or ATP synthesis, but larger reductions in COX activity are associated with a sharp decline in respiratory function (47,48). The amount of control that COX exerts on respiratory function is dependent on the type of cell lines and tissues (47,49,50). The relatively high rates of oxygen consumption in the 97% mutant cells suggest that, in these cell lines, COX may exert a low control strength on respiratory function.…”
Section: Discussionmentioning
confidence: 99%